2014
DOI: 10.1111/jipb.12127
|View full text |Cite
|
Sign up to set email alerts
|

Small auxin upregulated RNA (SAUR) gene family in maize: Identification, evolution, and its phylogenetic comparison with Arabidopsis, rice, and sorghum

Abstract: Small auxin-up RNAs (SAURs) are the early auxin-responsive genes represented by a large multigene family in plants. Here, we identified 79 SAUR gene family members from maize (Zea mays subsp. mays) by a reiterative database search and manual annotation. Phylogenetic analysis indicated that the SAUR proteins from Arabidopsis, rice, sorghum, and maize had divided into 16 groups. These genes were non-randomly distributed across the maize chromosomes, and segmental duplication and tandem duplication contributed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
77
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 84 publications
(119 reference statements)
4
77
2
Order By: Relevance
“…Genomic bioinformatic analyses have revealed that there are 81 SAURs (including two pseudogenes) in Arabidopsis (Hagen and Guilfoyle, 2002), 58 SAURs (including two pseudogenes) in rice (Jain et al, 2006), 18 SAURs in moss (Rensing et al, 2008), 71 SAURs in sorghum (Wang et al, 2010), 134 SAURs in potato (Wu et al, 2012), 99 SAURs in tomato (Wu et al, 2012), and 79 SAURs in maize (Chen et al, 2014). Typically, SAUR genes are not randomly distributed in the genome, as many of them are found in tandem arrays of extremely highly related genes in soybean (McClure et al, 1989), Arabidopsis (Hagen and Guilfoyle, 2002), rice (Jain et al, 2006), tomato (Wu et al, 2012), and maize (Chen et al, 2014). Tandem and segmental duplication events likely contributed to the expansion of the SAUR gene family (Wu et al, 2012; Chen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic bioinformatic analyses have revealed that there are 81 SAURs (including two pseudogenes) in Arabidopsis (Hagen and Guilfoyle, 2002), 58 SAURs (including two pseudogenes) in rice (Jain et al, 2006), 18 SAURs in moss (Rensing et al, 2008), 71 SAURs in sorghum (Wang et al, 2010), 134 SAURs in potato (Wu et al, 2012), 99 SAURs in tomato (Wu et al, 2012), and 79 SAURs in maize (Chen et al, 2014). Typically, SAUR genes are not randomly distributed in the genome, as many of them are found in tandem arrays of extremely highly related genes in soybean (McClure et al, 1989), Arabidopsis (Hagen and Guilfoyle, 2002), rice (Jain et al, 2006), tomato (Wu et al, 2012), and maize (Chen et al, 2014). Tandem and segmental duplication events likely contributed to the expansion of the SAUR gene family (Wu et al, 2012; Chen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, SAUR genes are not randomly distributed in the genome, as many of them are found in tandem arrays of extremely highly related genes in soybean (McClure et al, 1989), Arabidopsis (Hagen and Guilfoyle, 2002), rice (Jain et al, 2006), tomato (Wu et al, 2012), and maize (Chen et al, 2014). Tandem and segmental duplication events likely contributed to the expansion of the SAUR gene family (Wu et al, 2012; Chen et al, 2014). The genomic structures of SAUR genes show similar features.…”
Section: Introductionmentioning
confidence: 99%
“…Since the early 2000s, data on the enzyme hormone-dependent C-terminal domain phosphorylation has been accumulating (Palmgren, 2001;Takahashi, Hayashi, and Kinoshita, 2012;Chen, Hao, and Cao, 2014). It was shown that gibberellic acid enhances the phosphorylation of Thr-947, and cytokinin, on the contrary, reduces this process (Chen, Hao, and Cao, 2014).…”
Section: Plant Hormones and Growth Regulators In Modulation Of Pm Promentioning
confidence: 99%
“…It was shown that gibberellic acid enhances the phosphorylation of Thr-947, and cytokinin, on the contrary, reduces this process (Chen, Hao, and Cao, 2014). The binding of brassinosteroids to the BRI1 receptor resulted in rapid hyperpolarization (Caesar et al, 2011).…”
Section: Plant Hormones and Growth Regulators In Modulation Of Pm Promentioning
confidence: 99%
See 1 more Smart Citation